Peer-review mechanism for the biological and toxin weapons convention - Revill, James (United Nations New YorkUS, 2013)
Sets out a number of prerequisities for any peer-review system. Concludes by identifying a number of advantages and disadvantages of a peer-review process. Recommends that one useful preliminary step that states parties could undertake would be communication between counterparts in agencies with experience of peer-review mechanisms.